Removal of chromium from effluents of tannery industry by electrodialysis - Pilco Núñez, Alex (2018)
Chromium salts are chemical reagents widely used in the tannery industry because they are efficient for tanning animal skin, however, these salts are not completely fixed, so their remnants go to their effluents, seriously impacting the environment. The objective of this study was to remove chromium (VI) and total chromium from a tannery effluent using electrodialysis, for this purpose, a sample of an effluent from a tannery pilot plant was characterized and then a synthetic solution was prepared based on this, using an industrial grade chrome salt for tannery, then the limiting current was determined and electrodialysis tests were carried out with the 80, 100 and 120% of the limiting current. The results showed that the highest percentage of extraction and the lowest electricity consumption was 80% of the limiting current.